The Disordered Vaginal Microbiota Is a Potential Indicator for a Higher Failure of in vitro Fertilization - Kong, Yao; Liu, Zhaoxia; Shang, Qingyao; Gao, Yuan; Li, Xia; Zheng, Cihua; Deng, Xiaorong; Chen, Tingtao (Frontiers in Medicine, 2020)
Infertility belongs to one of the most common reproductive system diseases, and no effective treatment is available for this disease. In vitro fertilization (IVF) has been widely used to enhance the clinical pregnancy outcome, while its unsatisfied pregnancy rate with unknown reasons bring pressure and pain to countless families.To identify the possible cause of IVF failure, 555 patients were enrolled in the present study, their relevant clinical characteristics were determined, and their vaginal microbiota was monitored by high-throughput sequencing method. The results indicated that the age and endometrium thickness significantly affected the pregnancy success rate of pregnant patients (P group) and non-pregnant patients (NP group) receiving IVF (P<0.05), and high values of luteinizing hormone, estrogen and progesterone were observed from P group. Furthermore, the Partial Least Squares Discriminant Analysis (PLS-DA) indicated a different microbial composition in P group and NP group, and a higher microbial abundance had been identified in nonpregnant patients compared with pregnant patients. At phylum level, a high abundance of Firmicutes and Proteobacteria, and a lower abundance of Actinobacteria, Fusobacteria, and Bacteroidetes were obtained in pregnant patients compared with non-pregnant patients. At genus level, lower abundance of probiotic Lactobacillus (P=0.24), and higher abundance of pathogens Gardnerella (P=0.04) and Prevotella (P=0.02) were identified from non-pregnant patients. Therefore, the disordered microbiota, characterising by the reduction of probiotics and overgrowth of pathogens in non-pregnant patients, maybe used as a potential indicator for a higher IVF failure.